The functionalized amino acid (S)-Lacosamide subverts CRMP2-mediated tubulin polymerization to prevent constitutive and activity-dependent increase in neurite outgrowth - Wilson, Sarah M.; Moutal, Aubin; Melemedjian, Ohannes K.; Wang, Yuying; Ju, Weina; François-Moutal, Liberty; Khanna, May; Khanna, Rajesh (Frontiers in Cellular Neuroscience, 2014)
Activity-dependent neurite outgrowth is a highly complex, regulated process with important implications for neuronal circuit remodeling in development as well as in seizure-induced sprouting in epilepsy. Recent work has linked outgrowth to collapsin response mediator protein 2 (CRMP2), an intracellular phosphoprotein originally identified as axon guidance and growth cone collapse protein. The neurite outgrowth promoting function of CRMP2 is regulated by its phosphorylation state. In this study, depolarization (potassium chloride)-driven activity increased the level of active CRMP2 by decreasing its phosphorylation by GSK3β via a reduction in priming by Cdk5. To determine the contribution of CRMP2 in activity-driven neurite outgrowth, we screened a limited set of compounds for their ability to reduce neurite outgrowth but not modify voltage-gated sodium channel (VGSC) biophysical properties. This led to the identification of (S)-lacosamide ((S)-LCM), a stereoisomer of the clinically used antiepileptic drug (R)-LCM (Vimpat®), as a novel tool for preferentially targeting CRMP2-mediated neurite outgrowth. Whereas (S)-LCM was ineffective in targeting VGSCs, the presumptive pharmacological targets of (R)-LCM, (S)-LCM was more efficient than (R)-LCM in subverting neurite outgrowth. Biomolecular interaction analyses revealed that (S)-LCM bound to wildtype CRMP2 with low micromolar affinity, similar to (R)-LCM. Through the use of this novel tool, the activity-dependent increase in neurite outgrowth observed following depolarization was characterized to be reliant on CRMP2 function. Knockdown of CRMP2 by siRNA in cortical neurons resulted in reduced CRMP2-dependent neurite outgrowth; incubation with (S)-LCM phenocopied this effect. Other CRMP2-mediated processes were unaffected. (S)-LCM subverted neurite outgrowth not by affecting the canonical CRMP2-tubulin association but rather by impairing the ability of CRMP2 to promote tubulin polymerization, events that are